2019
DOI: 10.1021/acs.jafc.9b04587
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Protection of Astaxanthin from Oxidative Damage Induced by H2O2in RAW 264.7 Cells Based on1H NMR Metabolomics

Abstract: Astaxanthin (AST) is a fat-soluble and non-vitamin A source of carotenoid that can quench reactive oxygen species and it has strong antioxidant and anti-inflammatory abilities. Herein, we have used H 2 O 2 to establish a model of oxidative damage to RAW 264.7 cells and cells treated with vitamin C as the positive control group. The changes in metabolome were examined using 1 H NMR and the results demonstrated that H 2 O 2 treatment and various metabolic pathways such as amino acid, glucose, and glycerolipid me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…According to Mo et al [ 65 ], thiram may interfere with the metabolism of taurine and hypotaurine, pyrimidines, and glycerolipids, which in turn may cause OS by activating the Nrf2 signal pathway. Astaxanthin has been shown by Mei et al [ 66 ] to partially counteract the down-regulation of specific metabolic pathways, including glycerolipid metabolism, and reduce OS and cell death. In the lungs of rats modeled with sepsis-related lung injury, He et al [ 67 ] discovered that Liang-Ge decoction inhibited inflammatory responses, OS, apoptosis, and modulated metabolites associated with glycine, serine, and threonine metabolism, cysteine and methionine metabolism, inositol phosphate metabolism, and the TCA cycle.…”
Section: Discussionmentioning
confidence: 99%
“…According to Mo et al [ 65 ], thiram may interfere with the metabolism of taurine and hypotaurine, pyrimidines, and glycerolipids, which in turn may cause OS by activating the Nrf2 signal pathway. Astaxanthin has been shown by Mei et al [ 66 ] to partially counteract the down-regulation of specific metabolic pathways, including glycerolipid metabolism, and reduce OS and cell death. In the lungs of rats modeled with sepsis-related lung injury, He et al [ 67 ] discovered that Liang-Ge decoction inhibited inflammatory responses, OS, apoptosis, and modulated metabolites associated with glycine, serine, and threonine metabolism, cysteine and methionine metabolism, inositol phosphate metabolism, and the TCA cycle.…”
Section: Discussionmentioning
confidence: 99%
“…36 Then, ammonia could enter the urea cycle and α-ketoglutarate is metabolized through the tricarboxylic acid cycle. 28 The ANP supplement could decrease the level of ammonia and increase glutamic acid and glutamine contents, which could up-regulate the energy metabolism of the host cell. 37 Metabolic pathway results showed that glutamine and glutamic acid metabolism were inhibited in mice with CiMe-induced colitis, and the ANP supplement could reverse that.…”
Section: Discussionmentioning
confidence: 99%
“…Amino acids are the constituents of proteins and they are usually the forerunners in the host energy metabolism. 28 Phenylalanine and tryptophan are essential amino acids and they participate in dopamine, norepinephrine, and epinephrine biosynthesis. 29 Phenylalanine could increase the CD4 lymphocyte population 30 and CD4 lymphocytes could produce IL-10, which is an important factor in preventing colitis.…”
Section: Papermentioning
confidence: 99%
“…Murine RAW 264.7 macrophage cell line was acquired from American Type Culture Collection (ATCC) and cultured as reported by [ 15 ]. The cellular viability of RAW 264.7 was assessed by MTT assay as previously described by [ 16 ].…”
Section: Methodsmentioning
confidence: 99%